2022
DOI: 10.1039/d2nj01658c
|View full text |Cite
|
Sign up to set email alerts
|

A novel three-position molecular switch based on the transformations of a cyano-substituted pyrrol-2-one derivative

Mikhail Yu. Belikov,
Angelina G. Milovidova,
Mikhail Yu. Ievlev

Abstract: The possibility of creating the first representative of a novel group of molecular switches sensitive to the solvent, to the action of acid-base reagents and to temperature changes has been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The stabilization of the spectral pattern after Et 3 N addition was associated with the impossibility of subsequent addition of this base to the anion of AM 1 type, which can be formed upon the addition of various amines. It should also be noted that the principal possibility of the formation of structures AM 1 from OTCP 1 a and triethylamine was described earlier [29] supporting the discussion above.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The stabilization of the spectral pattern after Et 3 N addition was associated with the impossibility of subsequent addition of this base to the anion of AM 1 type, which can be formed upon the addition of various amines. It should also be noted that the principal possibility of the formation of structures AM 1 from OTCP 1 a and triethylamine was described earlier [29] supporting the discussion above.…”
Section: Resultssupporting
confidence: 80%
“…On the next step, electronic absorption spectra of chromophores 1 a – f in acetonitrile solution (50 μM) were recorded. The solvent was chosen due to the single report on reversible transformations of OTCP 1 a in acetonitrile [29] . The solutions of chromophores 1 a – f had an orange‐magenta color caused by an absorption band in the visible region of the spectrum centered at 494–512 nm (Figure 3, Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the literature showed that one of the methods for the synthesis of 2‐oxopyrroles with an ylidenemalononitrile fragment in the third position is the use of corresponding pyrrole‐2,3‐diones in reaction with malononitrile [37,38] . In this regard, we carried out a sequence of transformations based on the initial reaction of available trimethylsilyl ether of propiophenone with oxalyl chloride leading to the formation of known furan‐2,3‐dione 3 [39] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%